Cucumber mosaic virus among ornamental crops in the Russian Far East - V. F. Tolkach; Yu. G. Volkov; N. N. Kakareka; M. R. Aliev; M. Yu. Shchelkanov (Юг России: экология, развитие)
Aim. To summarise and analyse scientific data on Cucumber mosaic virus strains (CMV – Cucumber mosaic virus) (Martellivirales: Bromoviridae, Cucumovirus) isolated from ornamental plants in the Far East of the Russian Federation.   Discussion. The paper describes the genome structure and tripartite organization of CMV virions. Strains of this virus isolated from ornamental cultures in the south of the Russian Far East are described: Garden balsam, Common snapdragon, Dahlias, Hybrid gladiolus, Hybrid delphinium, Cambria, Indian canna, Cattleya, Tiger lily, Garden petunia, Primula obconica, Moth orchids, Fatshedera from Lize Freres, Weeping fig, Common hollyhock, Purple coneflower. The physicochemical properties (i. e. point of thermal inactivation, period of preservation of infectivity at a temperature of 20 °C, maximum dilution of juice causing disease of healthy plants) and the symptoms of these strains on a wide range of species and varieties of indicator plants are systematised according to the Russian Collection of East Asian Viruses, functioning at the Laboratory of Virology of the Federal Scientific Center for East Asia Terrestrial Biodiversity, Far Eastern Branch, Russian Academy of Sciences.   Conclusions. The limiting factor in the development of floriculture is infectious diseases, among which viral infections (including CMV) are of the greatest importance, demonstrating a high strain diversity in the south of the Russian Far East. Thus, the study of the biological, physico‐chemical, immunochemical and molecular biological properties of CMV is an urgent task, as it opens up the possibility of studying isolates of this virus and classifying its strains taking into account individual characteristics and kinship relationships.